2017
DOI: 10.1016/j.jiph.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A persistent antimicrobial resistance pattern and limited methicillin-resistance-associated genotype in a short-term Staphylococcus aureus carriage isolated from a student population

Abstract: The aim of the present study was to assess and compare the antimicrobial susceptibility pattern against a panel of antibiotics and molecular and methicillin resistance-associated genotypes of 120 carriage S. aureus isolates previously isolated from a student population at two isolation events within a one-month interval. The antibiotic susceptibility of isolates was determined using the Kirby-Bauer disc-diffusion method (cefoxitin by Etest). The MRSA was screened using polymerase chain reaction for the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
4
14
1
Order By: Relevance
“…However, in contrast to our findings, recent surveillance of S. aureus nasal carriers among preclinical and clinical medical students in Klang Valley, western Malaysia, detected a lower prevalence of MSSA (14%) with no MRSA isolated . The 15% (18/119) MRSA rate among S. aureus isolates in our study is higher than the 8.3% (10/120) previously reported among health science students in Malaysian universities .…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…However, in contrast to our findings, recent surveillance of S. aureus nasal carriers among preclinical and clinical medical students in Klang Valley, western Malaysia, detected a lower prevalence of MSSA (14%) with no MRSA isolated . The 15% (18/119) MRSA rate among S. aureus isolates in our study is higher than the 8.3% (10/120) previously reported among health science students in Malaysian universities .…”
Section: Discussioncontrasting
confidence: 82%
“…Commonly, HA‐MRSA strain would harbour SCC mec type I, II or III and does not frequently carry Panton–Valentine leukocidin ( pvl ) gene, whereas CA‐MRSA strain commonly carries SCC mec ‐IV or V and pvl gene . Previous studies in Malaysia from different localities and populations also indicated the presence of SCC mec ‐I and SCC mec ‐III in the nares of health science students living in the vicinity of the hospital and medical community . Among the 18 MRSAs isolated in our study, SCC mec ‐III (44%; 8/18 isolates) was the most common SCC mec type identified.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Staphylococcus aureus is a Gram positive and coagulase producing bacterium usually1 20-50% of the human population are often colonized with S. aureus. 2,3 Methicillin-resistant S. aureus (MRSA) is one of the major risk pathogens associated with evolution of antimicrobial resistance. Additionally, antibiotics from the macrolide-lincosamide-streptogramin B (MLS B ) family are usually drugs of choice for the treatment of staphylococcal infections.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates from this lineage were first detected in Kuwait in 2016 (21 isolates) and then in 2017 (10 isolates). CC96 MRSA isolates are rare in humans with only single isolates reported previously from Russia (Mendes et al, 2012) and Saudi Arabia (Senok et al, 2016;Mat Azis et al, 2017). However, ST96-MSSA is a common pathogen of rabbits, where it causes different infections (Mendes et al, 2012;Viana et al, 2015;Merz et al, 2016;Moreno-Grúa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%